Perineural Scar Prevention in Brachial Plexus Decompression Surgery: Clinical Outcomes Using a Bioresorbable Hydrogel Implant - Samantha Cervantes Valadez; Peyton Harris; Liam Cato; Yousef Tanas; Anthony Echo (HAND, 2026)
Background: Perineural scarring after peripheral nerve surgery is a known cause of persistent pain and reoperation. Brachial plexus decompression for neurogenic thoracic outlet syndrome (nTOS) carries a particularly high risk given the extent of dissection, scalenectomy, and the constant motion of the cervicothoracic region. Recurrence rates after complete decompression range from 7% to 30%. VersaWrap (Alafair Biosciences) is a bioresorbable hyaluronic acid/alginate hydrogel that physically blocks fibroblast access while allowing nutrient diffusion to the nerve. Its use has not previously been reported in brachial plexus surgery. Methods: We reviewed 94 patients who underwent supraclavicular brachial plexus decompression for nTOS at a single institution between 2014 and 2025. Forty-nine received VersaWrap around the brachial plexus trunks after neurolysis; 45 underwent the same procedure without a wrap. Primary outcomes were persistent neuropathic pain and reintervention for nTOS. Secondary outcomes included paresthesias, opioid use past 5 days, wound complications, and device-related adverse events. Results: Mean follow-up was 12 months for the entire cohort. Persistent neuropathic pain occurred in 2 VersaWrap patients (4.1%) versus 3 controls (6.7%). Reintervention was required in 1 VersaWrap patient (2%) versus 2 controls (4.4%). Postoperative paresthesias were noted in 4 VersaWrap patients (8.2%) versus 3 controls (6.7%). Opioid use beyond 5 days occurred in 2 VersaWrap patients (4.1%). No device-related complications were observed. Conclusions: VersaWrap was safe and well tolerated. Rates of persistent pain and reoperation were numerically lower in the VersaWrap group, though the study was not powered to detect significant differences. These results support further prospective evaluation of hydrogel barriers in high-risk peripheral nerve surgery.